2016
DOI: 10.1016/j.bbmt.2015.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Functionally Active HIV-Specific T Cells that Target Gag and Nef Can Be Expanded from Virus-Naïve Donors and Target a Range of Viral Epitopes: Implications for a Cure Strategy after Allogeneic Hematopoietic Stem Cell Transplantation

Abstract: Allogeneic HSCT can potentially cure HIV by eliminating infected recipient cells, particularly in the context of technologies that may confer HIV resistance to these stem cells. But to date, the Berlin patient remains the only case of HIV cure despite multiple attempts to eradicate infection with HSCT. One approach to improve this is to administer virus-specific T cells, a strategy that has proven success in preventing other infections post-transplant. While we have reported that broadly-HIV-specific T cells c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 17 publications
1
37
0
Order By: Relevance
“…While cure of chronic viral infections seemed improbable several years ago, HIV cure is currently an active research area with several investigational approaches, and at least one patient has been cured following hematopoietic stem cell transplantation (59). An assessment in HIV-1 seropositive individuals in the United Kingdom showed high interest in HIV-1 cure studies, and willingness to take experimental therapies in the absence of personal benefit (10).…”
Section: Introductionmentioning
confidence: 99%
“…While cure of chronic viral infections seemed improbable several years ago, HIV cure is currently an active research area with several investigational approaches, and at least one patient has been cured following hematopoietic stem cell transplantation (59). An assessment in HIV-1 seropositive individuals in the United Kingdom showed high interest in HIV-1 cure studies, and willingness to take experimental therapies in the absence of personal benefit (10).…”
Section: Introductionmentioning
confidence: 99%
“…HIV-specific T cells manufactured this way are currently being evaluated in the autologous setting (#NCT02208167) and studies utilizing donor-derived HIV-specific T cells after allogeneic HSCT are planned. 79 An alternative approach in the naïve donor is to transduce T cells with a TCR with known viral specificity. 80,81 Although this strategy offers a novel, rapid method to generate VSTs from naïve donors, it does impose the additional cost and regulatory requirements of gene transfer.…”
Section: Manufacturing T Cells With Virus Specificity From Virus-naïvmentioning
confidence: 99%
“…Autologous multiepitope-specific T cells are now in an ongoing clinical trial (NCT02208167). Another study demonstrated that multiepitope-specific T cells can be generated from HIV-naïve donors, opening up the possibility of antiviral T cell therapy in HIV + individuals with hematologic malignancies necessitating allogeneic HSCT [30].…”
Section: Multi-hiv Antigen-specific T Cellsmentioning
confidence: 99%